PENGARUH BUKU SAKU GIZI KESEHATAN REPRODUKSI TERHADAP MINAT PENCEGAHAN ANEMIA PADA WANITA PEKERJA - Mamat Mamat; Mardianti Mardianti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
The cause of the occurrence of anemia cases due to lack of knowledge. Pocketbook media is an alternative to meet the needs of a lack of knowledge. The purpose of this study was to find the effect of the reproductive health nutrition pocketbook on perceptions of behavior, subjective norms, attitudes, and behavioral interest in anemia prevention among female workers. The design used was an experimental questionnaire with a control group. The sample is female workers taken by purposive random sampling. The sample size was 119 divided into 2 groups, is the intervention group 54 samples and 65 samples as a control group. The pocketbook used for the intervention has been compiled and reviewed based on needs and expert studies. The data collected refer to the Theory of Planned Behavior (TPB) theory, taken online including perceptions of behavior control, subjective norms and attitudes, and interest in anemia prevention behavior. The data was processed using the SPPS program and then analyzed by an independent t-test. The results showed that there was a pocketbook influence on perceptions of behavioral control, subjective norms, and attitudes, which illustrated that the difference in the mean value of perceived behavioral control was greater in the intervention group 1.56 points, subjective norms of 2, 2 points and an attitude score of 3.0 points compared to the control group where all three have a p-value of 0.01. There was a pocketbook effect on interest with a difference in the average interest of 1.33 points, greater in the intervention group than in the control group with a p-value of 0.001. Referring to the results of media development, it needs to be improved in online forms such as E-books and other information media and there needs to be collaboration and coordination with related agencies